Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 6 - Section 6.5 - A General Factoring Strategy - Exercise Set - Page 462: 90



Work Step by Step

$ 3a^{2}+15ab+18b^{2}\qquad$... factor out the common term, $3$ $=3(a^{2}+5ab+6b^{2})$ ... Searching for two factors of $ac=6$ whose sum is $b=5,$ we find$\qquad 1$ and $6.$ Rewrite the middle term and factor in pairs: $=3(a^{2}+ab+6ab+6b^{2})=$ $=3[a(a+b)+6b(a+b)]$ = $3(a+b)(a+6b)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.